2017
DOI: 10.1093/annonc/mdw561
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib in pancreatic neuroendocrine tumors: updated progression-free survival and final overall survival from a phase III randomized study

Abstract: NCT00428597.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
137
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(142 citation statements)
references
References 14 publications
1
137
0
4
Order By: Relevance
“…The trial was terminated early after a higher number of serious adverse events (SAEs) and deaths were observed in the placebo arm compared with the sunitinib arm, and a difference in investigator-assessed PFS favoured sunitinib (hazard ratio [HR], 0.42, 95% confidence interval [CI], 0.26-0.66; p < 0.001; median 11.4 [7.4-19.8] vs. 5.5 [3.6-7.4] months) [5]. Five years after study closure, median (95% CI) overall survival (OS) was 38.6 (25.6-56.4) and 29.1 (16.4-36.8) months (HR, 0.73; 95% CI, 0.50-1.06; p = 0.094) with sunitinib and placebo, respectively; the lack of significance was probably due to the crossover, in which 69% of patients had switched from placebo to sunitinib [6].…”
Section: Introductionmentioning
confidence: 99%
“…The trial was terminated early after a higher number of serious adverse events (SAEs) and deaths were observed in the placebo arm compared with the sunitinib arm, and a difference in investigator-assessed PFS favoured sunitinib (hazard ratio [HR], 0.42, 95% confidence interval [CI], 0.26-0.66; p < 0.001; median 11.4 [7.4-19.8] vs. 5.5 [3.6-7.4] months) [5]. Five years after study closure, median (95% CI) overall survival (OS) was 38.6 (25.6-56.4) and 29.1 (16.4-36.8) months (HR, 0.73; 95% CI, 0.50-1.06; p = 0.094) with sunitinib and placebo, respectively; the lack of significance was probably due to the crossover, in which 69% of patients had switched from placebo to sunitinib [6].…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy, in none of these trials a significant OS benefit was demonstrated. [8][9][10][11][12][13][14][15] Conclusion: To date, published trials are comparable in design and efficacy, and the corresponding MCBS-FT score of 2-3 is consistent with the moderate clinical benefit seen while treating patients with advanced or metastatic NET. The fact that all trials rated equally in quite similar clinical settings reflects however one difficulty of the scale in its current version: as only one trial may be considered at once (except for meta-analyses), there is no additional information for optimal sequencing of treatment options added by the ESMO-MCBS scoring system; this has also previously been discussed for colorectal cancer and renal cell cancer in our pilot analysis.…”
Section: Results Neuroendocrine Tumoursmentioning
confidence: 53%
“…[8][9][10][11][12][13][14][15] Assessment of ESMO-MCBS scores for advanced NET revealed comparable results in all available data (all trials placebo controlled). The CLARINET and the PROMID trial represent two proof of principle studies demonstrating for the first time direct antiproliferative effects of somatostatin analogues for advanced midgut and pancreatic NET irrespective of progression status.…”
Section: Results Neuroendocrine Tumoursmentioning
confidence: 76%
See 1 more Smart Citation
“…Sunitinib is an oral, smallmolecule, multi-targeted tyrosine kinase inhibitor with activity against VEG-F and PDGF. A recent phase III trial randomized 171 patients with advanced well differentiated pNENs compared therapy with sunitinib versus placebo (65). The study was discontinued early because of the clear advantage of sunitinib versus the placebo group.…”
Section: Agents For Antiangiogeneismentioning
confidence: 99%